Discrimination of β-cyclodextrin/hazelnut (Corylus avellana L.) oil/flavonoid glycoside and flavonolignan ternary complexes by Fourier-transform infrared spectroscopy coupled with principal component analysis - Hădărugă, Nicoleta G.; Popescu, Gabriela; Gligor (Pane), Dina; Mitroi, Cristina L.; Stanciu, Sorin M.; Hădărugă, Daniel Ioan (Beilstein Journal of Organic Chemistry, 2023)
The goal of the study was the discrimination of β-cyclodextrin (β-CD)/hazelnut (Corylus avellana L.) oil/antioxidant ternary complexes through Fourier-transform infrared spectroscopy coupled with principal component analysis (FTIR–PCA). These innovative complexes combine the characteristics of the three components and improve the properties of the resulting material such as the onsite protection against oxidative degradation of hazelnut oil unsaturated fatty acid glycerides. Also, the apparent water solubility and bioaccessibility of the hazelnut oil components and antioxidants can be increased, as well as the controlled release of bioactive compounds (fatty acid glycerides and antioxidant flavonoids, namely hesperidin, naringin, rutin, and silymarin). The appropriate method for obtaining the ternary complexes was kneading the components at various molar ratios (1:1:1 and 3:1:1 for β-CD hydrate:hazelnut oil (average molar mass of 900 g/mol):flavonoid). The recovering yields of the ternary complexes were in the range of 51.5–85.3% and were generally higher for the 3:1:1 samples. The thermal stability was evaluated by thermogravimetry and differential scanning calorimetry. Discrimination of the ternary complexes was easily performed through the FTIR–PCA coupled method, especially based on the stretching vibrations of CO groups in flavonoids and/or CO/CC groups in the ternary complexes at 1014.6 (± 3.8) and 1023.2 (± 1.1) cm−1 along the second PCA component (PC2), respectively. The wavenumbers were more appropriate for discrimination than the corresponding intensities of the specific FTIR bands. On the other hand, ternary complexes were clearly distinguishable from the starting β-CD hydrate along the first component (PC1) by all FTIR band intensities and along PC2 by the wavenumber of the asymmetric stretching vibrations of the CH groups at 2922.9 (± 0.4) cm−1 for ternary complexes and 2924.8 (± 1.4) cm−1 for β-CD hydrate. The first two PCA components explain 70.38% from the variance of the FTIR data (from a total number of 26 variables). Other valuable classifications were obtained for the antioxidant flavonoids, with a high similarity for hesperidin and naringin, according to FTIR–PCA, as well as for ternary complexes depending on molar ratios. The FTIR–PCA coupled technique is a fast, nondestructive and cheap method for the evaluation of quality and similarity/characteristics of these new types of cyclodextrin-based ternary complexes having enhanced properties and stability.
Keywords: antioxidant; cyclodextrin; flavonoid; hazelnut vegetable oil; ternary supramolecular inclusion complex